BUSTRACKER: Cloud based bus tracking application - Alsewari, Abdulrahman A.; KabashI Kathir, Sharafeldin; Saeed, Mohammed Samih (2021)
Public transportation is a new and facilitated service which enables peoples to reach their desired destination without the need to use their personal vehicles. However, low accuracy of the bus schedules tend to cause many problems for the bus passengers. Moreover, most of the time,the bus will not arrive on the time which has been already provided on the schedule due to many causes such as traffic jam.